Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1046/j.1472-765x.2001.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of cellular polysaccharides in the formation and stability of aerobic granules

Abstract: Aims: This paper attempts to investigate the role of cellular polysaccharides in the formation and stability of aerobic granules. Methods and Results: Three column sequential aerobic sludge blanket reactors (R1, R2 and R3) were operated at a super®cial air up¯ow velocity of 0á3 cm s ±1 , 1á2 cm s ±1 and 2á4 cm s ±1 , respectively. Aerobic granules appeared at cycle 42 in R2 and R3 with a mean size of 0á37 mm in R2 and 0á35 mm in R3, however, aerobic granulation was not observed in R1. After the formation of ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
138
3
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(164 citation statements)
references
References 17 publications
10
138
3
2
Order By: Relevance
“…As in other microbial aggregates, such as biofi lms and biofl ocs, the EPS produced in biogranules are also composed of variable amounts of proteins, polysaccharides, nucleic acids, humic-like substances, lipids and glycoproteins, but the content of EPS in biogranules have been found to be much higher than that of biofl ocs and biofi lms [3]. Moreover, extracellular polymers likely play an important role in maintaining the structural and functional integrity of the granule.…”
Section: Biogranules and Metal Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other microbial aggregates, such as biofi lms and biofl ocs, the EPS produced in biogranules are also composed of variable amounts of proteins, polysaccharides, nucleic acids, humic-like substances, lipids and glycoproteins, but the content of EPS in biogranules have been found to be much higher than that of biofl ocs and biofi lms [3]. Moreover, extracellular polymers likely play an important role in maintaining the structural and functional integrity of the granule.…”
Section: Biogranules and Metal Removalmentioning
confidence: 99%
“…Although, these biogenic polymers mediate contact and exchange processes with biotic and abiotic environments, they may not be essential for growth and viability in free-living bacterial cultures. But during growth under natural environment, bacterial EPS play important role in cell adhesion, formation of microbial aggregates such as biofi lms, fl ocs, sludges and biogranules [2][3][4] and protect cells from hostile environments. They are also involved in the degradation of particulate substances, sorption of dissolved materials including heavy metals, [5] leaching of minerals from sulphidic ores as well as biocorrosion [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is not fully understood what factors increase EPS formation, although several researchers hypothesize that hydraulic shear may contribute (21). Tay et al (21) reported that increased aeration rates in a granular SBR resulted in an increased polysaccharide content and that granular sludge disintegrated when polysaccharides were lost from the system. Aerobic granules have also failed to form in systems with reduced aeration rates (6,22).…”
mentioning
confidence: 99%
“…PS has been reported as a polymeric viscous material that can stick to microbes and enhance the aggregation of microbes. In addition, the filamentous PS among the microbes can connect the dispersive microbes and the communities [30]. Therefore, the fewer PS of R3, relative to R1 and R2, partially resulted in the poor stability of granular sludge.…”
Section: The Stability Of Aerobic Granular Sludgementioning
confidence: 99%